Naskah-Naskah Keislaman Pandalungan: Islamic Manuscripts of Pandalungan - Muhammad Ardiansyah (Fenomena, 2015)
This paper is more of a report on preservation, conservation, and reconstruction activities of Islamic intellectual heritage through the inventory of manuscripts found in the Pandalungan region. This is important given the discovery of many manuscripts in poor and neglected conditions. The manuscripts themselves have yet to be explored in terms of their content and historical dimensions. The content and historical dimensions of these manuscripts can provide valuable information and knowledge for historiographical studies and the social history of Islamic intellectualism in the Pandalungan region. This initiative is an initial effort to prepare a database of Islamic manuscripts in Pandalungan, which can be used as a basis for further research on the intellectual heritage of Indonesian Islam, particularly in Pandalungan. Thus, these manuscripts will remain readable and alive as dynamic entities within communities that continue to evolve. The study of these manuscripts is also expected to reconstruct the intellectual heritage and social history of past societies. Through these manuscripts, we hope to write the social history and intellectual traditions of Pandalungan Islam from an "insider" perspective, not an "outsider" one. Philology serves as the approach—loosely applied—in this activity. This approach is based on the assumption that manuscripts, as heritage, contain thoughts, emotions, traditions, customs, and cultures that once existed and are still relevant to contemporary conditions. Tulisan ini lebih merupakan laporan kegiatan preservasi, pelestarian, dan rekonstruksi khazanah intelektual keislaman melalui inventarisasi naskah-naskah yang terdapat di wilayah Pandalungan. Ini penting dilakukan mengingat banyak ditemukan naskah-naskah dengan kondisi yang memprihatinkan, tak terawat. Naskah-naskah itu sendiri belum tergali dari segi content dan dimensi kesejarahannya. Content dan dimensi kesejarahan naskah tersebut dapat memberikan informasi maupun pengetahuan yang berharga dalam kajian historiografi maupun sejarah sosial intelektual Islam di wilayah Pandalungan. Kegiatan ini merupakan ikhtiar awal menyiapkan database naskah-naskah keislaman di wilayah Pandalungan yang dapat digunakan sebagai bahan studi lanjut bagi penelitian warisan intelektual Islam Nusantara, khususnya di wilayah Pandalungan. Naskah-naskah tersebut, dengan demikian, akan terbaca dan tetap hidup sebagai sesuatu yang bersifat dinamis, dalam komunitas yang terus bergerak dan berubah. Kajian naskah-naskah ini juga diharapkan mampu merekonstruksi khazanah intelektual dan sejarah sosial kehidupan masyarakat di masa lalu. Dari khazanah naskah-naskah ini kita berharap bisa menulis sejarah sosial dan tradisi intelektual keislaman Pandalungan dari perspektif “kita”, bukan “orang lain.” Filologi menjadi instrumen pendekatan –yang digunakan secara longgar– dalam kegiatan ini. Pendekatan ini berangkat dari asumsi mengenai karakteristik manuskrip sebagai heritage yang diduga mengandung buah pikiran, perasaan, tradisi, adat-istiadat, dan budaya yang pernah ada, dan dianggap masih relevan dengan kondisi kekinian.